TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PINJAMAN MODAL YANG DITERIMA KOPERASI JASA KEUANGAN SYARIAH (KJKS) NURUL FALAH DARI BANK JABAR BANTEN KCP SAYATI - Sidiq Permana; Yusuf Ajazy (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
ABSTRACTSharia Financial Services Cooperative (KJKS) Nurul Falah in meeting the needs of KJKS members impose some savings, including mandatory special savings, mandatory savings, and voluntary savings. In addition, KJKS in fulfilling its operational capital absorbed loans from third parties namely banks and non-banks. KJKS Nurul Falah absorbed a loan from Bank Jabar Banten which operated using the interest system.This study aims to determine: 1) Background KJKS Nurul Falah to borrow from Bank Jabar Banten. 2) The process of capital granting from Bank Jabar Banten to KJKS Nurul Falah. 3) The relevance of muamalah fiqih to capital loan KJKS Nurul Falah from Bank Jabar Banten.The research method used is descriptive research method, which is explaining about the view of sharia economic law on capital received KJKS Nurul Falah from Bank Jabar Banten. Sources of data there are two kinds, namely: 1) Primary data source (from the administrators or employees KJKS Nurul Falah). 2) Secondary data sources (from archives and books relating to the problem under investigation). Data obtained by interview and literature study.The results of this research, first. Background KJKS Nurul Falah to do capital loan to Bank Jabar Banten, because: 1). Doing business with Sharia Bank is not profitable. 2). Islamic banks can not afford to monitor every customer. Second, the process of providing capital from Bank Jabar Banten using two contracts, namely: 1). People's Business Credit (KUR). 2) Credit cash collateral. Third, Relevance fiqih muamalah about the capital received KJKS Nurul Falah from Bank Jabar Banten, there is a permit and there is a ban. The possible reasons are that there are exceptions to interest loans: 1) Emergency. 2) Not doubled. 3) Legal Entity and Law of Taklifi. As for the reasons that prohibit the verses of Al-Quran about usury, the hadith of the Prophet, the rules of ushul fiqih, the opinion of the scholars in the country and abroad, and Fatwa DSN MUI NO.04 / MUI About interest (interest / interest).The conclusion of this research is that the capital received by KJKS Nurul Falah from Bank Jabar Banten is irrelevant to the existing legal basis, such as: Al-Qura'an, Hadith, fiqih muamalah, legal search with ushul fiqih method, opinion The clerics, the MUI fatwa, although some allow the interest, but the source of the law for the acquisition is less strongly the legal arguments.